2016
DOI: 10.1101/090886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pervasive Antagonistic Interactions Among Hybrid Incompatibility Loci

Abstract: Species barriers, expressed as hybrid inviability and sterility, are often due to epistatic interactions between divergent loci from two lineages. Theoretical models indicate that the strength, direction, and complexity of these genetic interactions can strongly affect the expression of interspecific reproductive isolation and the rates at which new species 5 evolve. Nonetheless, empirical analyses have not quantified the frequency with which loci are involved in interactions affecting hybrid fitness, and whet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…A number of studies have investigated epistasis among pairs or triple sets of deleterious mutations, but the findings are mixed (105)(106)(107) . Sometimes the combined effect is the sum of the individual effects (additive/no epistasis), sometimes it is less than predicted from the individual effects (antagonistic/positive epistasis) (108,109) , and sometimes it is more than predicted (synergistic/negative epistasis) (110) . Among these three scenarios, antagonistic epistasis seems to be most common (104,111) .…”
Section: Combining Mutations and Epistasismentioning
confidence: 99%
“…A number of studies have investigated epistasis among pairs or triple sets of deleterious mutations, but the findings are mixed (105)(106)(107) . Sometimes the combined effect is the sum of the individual effects (additive/no epistasis), sometimes it is less than predicted from the individual effects (antagonistic/positive epistasis) (108,109) , and sometimes it is more than predicted (synergistic/negative epistasis) (110) . Among these three scenarios, antagonistic epistasis seems to be most common (104,111) .…”
Section: Combining Mutations and Epistasismentioning
confidence: 99%
“…What explains this mismatch between the RNA data and the Orr model? One possibility is that some inviable introgressions are caused by multiple DMIs (Guerrero et al 2016). For example, imagine two genotypes, 1 and 2, divergent at multiple loci…”
Section: Some Inviable Introgressions Are Caused By Multiple Dmis In mentioning
confidence: 99%
“…For example, the individual segments introgressed in Moyle and Nakazato (2010) included approximately 2-4% of the genome, and likely contained hundreds of genes. Second, individual alleles might participate in multiple DMIs, specially if complex DMIs are common (Guerrero et al 2016).…”
mentioning
confidence: 99%
“…Regardless of the evolutionary forces driving faster--X (Z) evolution (positive selection or relaxed negative selection), its implications for the genetic basis of hybrid dysfunction are clear: the X chromosome will disproportionally contribute to between--species Dobzhansky--Muller incompatibilities (DOBZHANSKY 1937;MULLER 1942;COYNE AND ORR 1989). Even a slightly elevated substitution rate on the X chromosome will be amplified in hybrids, as the number of incompatibilities increases exponentially with divergence time (ORR 1995;TURELLI AND ORR 2000;MATUTE et al 2010;MOYLE AND NAKAZATO 2010;GUERRERO et al 2017). Mapping studies in a 6 variety of species including mice, Lepidoptera, and Drosophila have shown that the factors having the largest effects on hybrid dysfunction, particularly hybrid male sterility, are X--linked (COYNE AND ORR 1989;COYNE et al 1991;COYNE 1992; COYNE AND ORR 2004).…”
mentioning
confidence: 99%